Canonical wnt signaling is required for commissural axon guidance - Avilés, Evelyn C. (Dev Neurobiol, 2015)
Morphogens have been identified as guidance cues for postcrossing commissural axons in the spinal cord. Shh has a dual effect on postcrossing commissural axons: a direct repellent effect mediated by Hhip as a receptor, and an indirect effect by shaping a Wnt activity gradient. Wnts were shown to be attractants for postcrossing commissural axons in both chicken and mouse embryos. In mouse, the effects of Wnts on axon guidance were concluded to depend on the planar cell polarity (PCP) pathway. Canonical Wnt signaling was excluded based on the absence of axon guidance defects in mice lacking Lrp6 which is an obligatory coreceptor for Fzd in canonical Wnt signaling. In the loss‐of‐function studies reported here, we confirmed a role for the PCP pathway in postcrossing commissural axon guidance also in the chicken embryo. However, taking advantage of the precise temporal control of gene silencing provided by in ovo RNAi, we demonstrate that canonical Wnt signaling is also required for proper guidance of postcrossing commissural axons in the developing spinal cord. Thus, axon guidance does not seem to depend on any one of the classical Wnt signaling pathways but rather involve a network of Wnt receptors and downstream components. © 2015 Wiley Periodicals, Inc. Develop Neurobiol 76: 190–208, 2016